Monetary union, asymmetric productivity shocks and fiscal insurance: An analytic discussion of welfare issues - Kenneth M. Kletzer (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1998)
This paper addresses arguments that a system of fiscal insurance between member states of the European Union is needed to act in replacement of nominal exchange rate flexibility as an automatic stabilizer under monetary union. Many authors have argued or assumed that asymmetric real macroeconomic fluctuations pose an important threat to the success of monetary unification and that some manner of fiscal insurance is missing from plans to cope with a common currency. A theoretical model economy in which production is subject to asymmetric national shocks is used to analyze the benefits of fiscal insurance for allocative efficiency under monetary union in comparison with resource allocation under a flexible nominal exchange rate regime. It is shown that whether national markets in goods and services are arbitraged or there is pricing-to-market matters for assessing the usefulness of fiscal insurance for efficiency as well as for assessing the macroeconomic costs of monetary union. The paper argues that the benefits of fiscal insurance for allocative efficiency may be increased little by monetary unification. Fiscal insurance may not be an essential or even desirable companion to a common currency.
Keywords: F41; F42; E6; 330; monetary union; exchange rate regimes; fiscal federalism